Posterior division of ipsilateral C7 transfer to C5 for shoulder abduction limitation - Huang, Xinying; You, Zongqi; Xiang, Yaoxian; Dai, Junxi; Jiang, Junjian (Frontiers in Neurology, 2023)
Background: Reparation of C5 by proximal selective ipsilateral C7 transfer has been reported for the treatment of neurogenic shoulder abduction limitation as an alternative to the reparation of suprascapular nerve (SSN) and axillary nerve (AXN) by distal nerve transfers. However, there is a lack of evidence to support either strategy leading to better outcomes based on long-term follow-up. Objective: To investigate the safety and long-term outcomes of posterior division of ipsilateral C7 (PDIC7) transfer to C5 in treating neurogenic shoulder abduction limitation. Methods: 27 cases with limited shoulder abduction caused by C5 injury (24 cases of trauma, 2 cases of neuritis, and 1 case of iatrogenic injury) underwent PDIC7 transfer to the C5 root. 12 cases (11 cases of trauma and 1 case of neuritis) of C5 injury underwent spinal accessory nerve (SAN) transfer to SSN plus triceps muscular branch of radial nerve (TMBRN) transfer to AXN. The patients were followed up for at least 12 months for muscle strength and shoulder abduction range of motion (ROM). Results: In cases that underwent PDIC7 transfer, the average shoulder abduction was 105.9° at 12-month follow-up. 26 of 27 patients recovered at least M3 (13 reached M4) (Medical Research Council Grading) of deltoid. In cases that underwent SAN transfer to SSN plus TMBRN to AXN, the average shoulder abduction was 84.6° at 12-month follow-up. 11 of 12 patients recovered at least M3 (4 reached M4) of deltoid. Conclusions: PDIC7 transfer is a one-stage, safe, and effective surgical procudure for patients with neurogenic shoulder abduction limitation.